A 3D scene analysis framework and descriptors for risk evaluation - Dupre, R.; Argyriou, V.; Greenhill, D.; Tzimiropoulos, G. (2015)
In this paper we evaluate the notion of scene analysis with regard to risk. We consider the problem of evaluating risk and potential hazards in an environment and providing a quantified risk score. A definition of risk is given incorporating two elements; Firstly scene stability, where Newtonian Physics are introduced into the scene analysis process, evaluating object stability within a scene. The effectiveness of which is demonstrated by conducting experiments on several scenes including a variety of stability levels. Secondly the analysis of the intrinsic risk related properties of an object, which is estimated using learning techniques and the utilisation of the 3D Voxel HOG descriptor, analysed against the state-of-the-art descriptors. Finally a new dataset is provided that is designed for scene analysis focusing on risk evaluation.